Implementation of a Gas Leakage Detection System Using the MQ-6 Sensor - Alexander Tommy (Brilliance: Research of Artificial Intelligence, 2022)
The role of gas at this time is very important for human life. The use of gas is expanding from household, industrial to transportation needs.Remember the depletion of petroleum supplies. This makes gas as an alternative fuel to replace the main role of petroleum. The risk of using gas as fuel is the occurrence of gas leaks which can have an impact on large-scale fires. A detection system is designed to detect gas leaks with the MQ-6 sensor and solenoid valve to close the gas line. The research was conducted by testing the voltage from the sensor using a predetermined program. The maximum reading distance from the gas sensor is 18 cm with a time of 45.26 seconds based on tests carried out by narrowing the gas exit path to provide a faster rate effect so that the sensor can detect gas.